Vitamin D in respiratory viral infections: a key immune modulator?. Issue 14 (30th May 2023) - Vaghari-Tabari, Mostafa; Mohammadzadeh, Iraj; Qujeq, Durdi; Majidinia, Maryam; Alemi, Forough; Younesi, Simin; Mahmoodpoor, Ata; Maleki, Masomeh; Yousefi, Bahman; Asemi, Zatollah
Abstract: Respiratory viral infections are common respiratory diseases. Influenza viruses, RSV and SARS-COV2 have the potential to cause severe respiratory infections. Numerous studies have shown that unregulated immune response to these viruses can cause excessive inflammation and tissue damage. Therefore, regulating the antiviral immune response in the respiratory tract is of importance. In this regard, recent years studies have emphasized the importance of vitamin D in respiratory viral infections. Although, the most well-known role of vitamin D is to regulate the metabolism of phosphorus and calcium, it has been shown that this vitamin has other important functions. One of these functions is immune regulation. Vitamin D can regulate the antiviral immune response in the respiratory tract in order to provide an effective defense against respiratory viral infections and prevention from excessive inflammatory response and tissue damage. In addition, this vitamin has preventive effects against respiratory viral infections. Some studies during the COVID-19 pandemic have shown that vitamin D deficiency may be associated with a higher risk of mortality and sever disease in patients with COVID-19. Since, more attention has recently been focused on vitamin D. In this article, after a brief overview of the antiviral immune response in the respiratory system, we will review the role of vitamin D in regulating the antiviral immune response comprehensively. Then we will discuss the importance of this vitamin in influenza, RSV, and COVID-19.